Student technical report on the participation at ANT-XXIII/4 cruise: bathymetric survey in Bellingshausen and Amundsen Seas, West Antarctic, South Pacific Ocean - Lemenkova, Polina (2006)
This work presents the student technical report of the participant at Bathymetry group at the R/V ’Polarstern’ cruise, AWI. The expedition is organized to the western sector of Antarctica, the South Pacific (Bellingshausen Sea, Amundsen Sea). The main goal of the Bathymetry group was to conduct high-resolution multispectral surveys of the seafloor topography along the ship's route, map sampling points of the geological sampling, interpret gravimetric measurements and expand the World database of the seafloor mapping, in particular, updating seafloor topography data for an international map GEBCO. As a result of the work, the seafloor topography on selected areas of the Amundsen and Bellingshausen seas was surveyed and maped using Hydrosweep DS-2, Caris HIPS, GMT, ArcGIS. Technological workflow, research methodology and geological description of the study area are presented in the report. info:eu-repo/semantics/published